The Sensitivity Analysis of Dragon Fruit Business in Ranomeeto District South Konawe Regency - Mutmainnah, Mutmainnah; Abdi, Abdi; Limi, Muhammad Aswar (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2022)
This research aims to find out the sensitivity of financial viability of dragon fruit farming in Ranomeeto Village, Ranomeeto District of South Konawe Regency. This research was conducted in Ranomeeto District, Ranomeeto South Konawe Regency of Southeast Sulawesi Province. The study took place from April 2021 to March 2022. The object of this study is the farming of the dragon fruit Abu Wafiq. This study uses case study methods with quantitative data analysis. This research aims to determine the feasibility of dragon fruit farming in terms of financial aspects. Financial aspects are analyzed by the Present Net method Value.Net B/C Ratio. Internal Rate of Return. Payback Period, as well as Sensitivity Analysis. The data used in this study are primary data and secondary data. The data retrieval techniques used are interviews and recording. From the study results obtained, the value of NPV = IDR13.731.275. Net B/C = 1.36. IRR = 61% and PP = 1.55 or 1 year 5 months. This effort is worth working on financially. In addition, based on the calculation of sensitivity analysis. Abu Wafiq dragon fruit farming is worth running when there is a 13% decrease in production and an increase in operating costs by 63%. If the change exceeds the tolerance limit determined, the business becomes unfit to run because the resulting NPV is smaller than 0 or negative